The Influence of Social Media Marketing Features on Purchase Decisions Riverside Forest Football Club Football Club's Jersey: Brand Trust As A Mediator - Fahmi Zain Idris; Dedi Iskamto (Eduvest - Journal of Universal Studies, 2025)
In analyzing the factors of consumer purchasing decisions through social media marketing, companies need to pay attention to the features in social media marketing that influence consumer purchasing decisions. This study aims to analyze the effect of features in social media marketing, namely: interactivity, informativeness, entertainment, and perceived relevance on purchasing decisions for Riverside Forest Football Club Jersey through brand trust as a mediator variable. This research uses quantitative methods. Data collection techniques are conducted through questionnaires distributed to supporters who have bought Riverside Forest Football Club Jerseys and follow their social media. This study uses a non-probability sampling method of purposive sampling with the Cochran formula for sample selection. Hypothesis testing is then conducted using the PLS-SEM (Partial Least Squares Structural Equation Modeling) approach. The data analysis techniques used are descriptive analysis and Partial Least Square (PLS) analysis. Theoretically, this study advances the current literature by exploring the mediating effect of brand trust among the four features of social media marketing and purchase decisions.